Flouting Maxim in “The Hundred-Foot Journey Movie”: An Opportunity to Improve Students’ Intercultural Literacy - Yustika, Leilya Sari; Setiawan, Slamet; Retnaningdyah, Pratiwi (State institute of islamic studies salatiga, 2022)
Facing the advancement of the technology era, there is increasing awareness about integrating intercultural communicative competence in the English language teaching process. Because many people from diverse cultural backgrounds talk in English, students should acquire that competence to compete globally. To produce appropriate conversation, Grice proposes four maxims that should be obeyed, called cooperative principles. However, because of a cross-cultural situation, someone can flout the maxim as part of communication. Therefore, the present study discusses the type and the reason for flouting maxims done by the characters in a movie which is a good learning medium to teach in a classroom. Furthermore, this study wanted to explore the cause of why the movie could be an opportunity for the teacher to increase students’ intercultural literacy through the English teaching and learning process. The data gathered from the movie script and the character’s behavior in a cross-cultural situation will be analyzed through content and thematic analysis. The result showed the figures of the movie flouted the maxim of quantity, quality, relevance, and manner. Humor intention, conviviality, enmity, elaborate explanation, prestige, mocking, and stating opinion were found in the movie as the characters’ motivation why they flout the maxim. The movie had an opportunity to improve students’ intercultural literacy by studying the characters’ communication and behavior. It contained understanding, competence, attitude, participation, and language that could equip students in improving their intercultural literacy.Keywords: Flouting maxim, Intercultural literacy, Movie Study